PENGEMBANGAN MEDIA FLIPBOOK DIGITAL MENGGUNAKAN APLIKASI HEYZINE PADA PEMBELAJARAN IPAS DI KELAS V SEKOLAH DASAR - Denisa, Salsa Billa; Astimar, Nelly (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the need for innovation in the world of education that utilizes technology to support learning in schools. Even though the existing facilities are sufficient to create learning media. This research aims to develop digital flipbook media using heyzine in science and science learning in class V elementary school that is valid, practical and effective. This type of research is development research (R&D) with the ADDIE model including analysis, design, development, implementation and evaluation. Data from this research were obtained from validation results, practicality questionnaires, pre-test and post-test questions. The validation sheet is filled in by material, language and media experts. Then a trial was carried out at SDN 21 Bandar Buat, Padang city by 16 people, consisting of 8 boys and 8 girls in class V. The results of this research obtained learning media in the form of digital flipbooks which were valid, practical and effective. The overall validation results obtained a percentage of 94.73% in the